Factors affecting dysbiosis of the gut microbiota in the elderly and the progress of interventions in traditional Chinese and Western medicine - Zhi-Jun Zhang; Ru Gao; Yu-Tong Lu; Zhi-Liang Zuo; Zhi-Liang Zuo; Yu-Huan Li; Shan Liu; Si-Yuan Song; Yi Wang; Hongyan Lai (Frontiers in Cellular and Infection Microbiology)
As the population ages, intestinal health in the elderly has become a key area of concern, with gut microbiota dysbiosis emerging as a significant issue. This review summarizes the factors influencing dysbiosis and interventions from both traditional Chinese medicine (TCM) and Western medicine, offering a reference for future research. A comprehensive search of global databases up to March 2024 identified 617 original studies on gut microbiota dysbiosis in individuals aged 65 and older. After applying strict PRISMA guidelines, 20 articles met the inclusion criteria. Key findings are summarized in four areas: 1) the definition and mechanisms of dysbiosis, 2) evaluation tools for gut microbiota imbalance, 3) factors contributing to dysbiosis in the elderly, and 4) pharmacological treatments. Both TCM and Western medicine offer unique advantages in managing gut microbiota dysbiosis, and the choice of intervention should be tailored to the individual’s condition. Future research should focus on optimizing integrated TCM and Western medicine approaches to improve outcomes for elderly patients with gut microbiota dysbiosis.